Kompetensi Literasi Digital Mahasiswa STKIP ‘Aisyiyah Riau - Khairi Murdy; Asri Neli Putri (Universitas Negeri Padang, 2020)
This research is to study the digital literacy competence of all STKIP Aisyiyah Riau students. This research was conducted using quantitative descriptive. Data obtained using a questionnaire filled out by students. Data were analyzed by calculating the Respondents' Level of Achievement. The results of this study indicate the digital literacy ability of students viewed from the indicator Internet Search, Hypertext Directions, Information Content Evaluation, and Knowledge Assembly shows a value of 77.1 and this value corresponds to the High category.